Effect of Environmental Enrichment Within Cages on Production and Welfare in Laying Hens - U Özentürk; A Uysal (Brazilian Journal of Poultry Science)
ABSTRACT This study aims to compare the effects of conventional cage systems (CC) and environmentally enriched cage systems (EEC) (which include nest boxes, perches, and pecking stones) on the productivity and welfare of laying hens, also considering the responses of two genotypes - Hyline Brown (HB) and Isa Tinted (IT). A total of 280 hens were evaluated for production (egg production, cracked eggs, mortality), welfare (keel bone damage, feather score, health score, footpad dermatitis, body condition, beak and claw lengths), and stress (heterophile/lymphocyte ratio, tonic immobility). Hens in CC produced more eggs (p<0.01) but had a higher incidence of cracked eggs (p<0.001). Hens in CC exhibited more feather loss, comb and cloacal wounds, and footpad dermatitis (p<0.05), while EEC hens had more keel bone damage (p<0.01). HB hens had higher productivity (86.07% vs. 82.01%) and lower cracked egg rates (0.19% vs. 0.92%) compared to IT (p<0.01). IT hens had higher mortality and stress (p<0.001). Welfare indicators favored HB hens across all parameters, except footpad dermatitis (p<0.05). While EEC lowered egg production, the reduced cracked egg rate and better welfare outcomes, such as improved feather coverage and fewer injuries, suggest advantages. HB outperformed IT in productivity, stress tolerance, and welfare across both systems.